Vegetation structure and floristic composition at habitat Rafflesia patma Blume in Pananjung Pangandaran Nature Reserve, West Java, Indonesia - Adnan, Bahana Aditya; Hadisusanto, Suwarno; Purnomo, Purnomo (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2023)
Rafflesia patma Blume is a plant endemic to Pangandaran, West Java, which is protected because of its rare status. This study aims to study the composition of the floristic vegetation that supports the life of R. patma in the Pananjung Pangandaran Nature Reserve, West Java. The research was conducted using a survey method with a purposive sampling technique and sampling using quadrat. The data obtained were then analyzed using the Importance Value Index (IVI), Shannon-Wiener index, and Evenness index. The results showed that R. patma in the Pananjung Pangandaran Nature Reserve lived as a parasite on the roots and stems of Tetrastigma leucostaphylum. The floristic composition of the habitat of R. patma in the Pananjung Pangandaran Nature Reserve, West Java, consisted of 251 individuals divided into 28 species. The plant species with the highest Importance Value Index (IVI) were Syzygium antisepticum, Stephania capitata, Casearia sp., and Buchanania arborescens for the sapling category, as well as Syzygium antisepticum and Vitex pubescens for the tree category. The condition of the vegetation around the habitat of R. patma is quite dense with the diversity index values obtained belonging to the moderate level of diversity. The highest diversity index at the sapling level was found at the Cilegon location with an H' value of 2.14 and the highest diversity index at the tree level was found at the Gua Parat location with an H' value of 1.5.